A Novel Regulator of Activation-Induced Cytidine Deaminase/APOBECs in Immunity and Cancer: Schrödinger’s CATalytic Pocket - King, Justin J.; Larijani, Mani (Frontiers in Immunology, 2017)
Activation-induced cytidine deaminase (AID) and its relative APOBEC3 cytidine deaminases boost immune response by mutating immune or viral genes. Because of their genome-mutating activities, AID/APOBECs are also drivers of tumorigenesis. Due to highly charged surfaces, extensive non-specific protein–protein/nucleic acid interactions, formation of polydisperse oligomers, and general insolubility, structure elucidation of these proteins by X-ray crystallography and NMR has been challenging. Hence, almost all available AID/APOBEC structures are of mutated and/or truncated versions. In 2015, we reported a functional structure for AID using a combined computational–biochemical approach. In so doing, we described a new regulatory mechanism that is a first for human DNA/RNA-editing enzymes. This mechanism involves dynamic closure of the catalytic pocket. Subsequent X-ray and NMR studies confirmed our discovery by showing that other APOBEC3s also close their catalytic pockets. Here, we highlight catalytic pocket closure as an emerging and important regulatory mechanism of AID/APOBEC3s. We focus on three sub-topics: first, we propose that variable pocket closure rates across AID/APOBEC3s underlie differential activity in immunity and cancer and review supporting evidence. Second, we discuss dynamic pocket closure as an ever-present internal regulator, in contrast to other proposed regulatory mechanisms that involve extrinsic binding partners. Third, we compare the merits of classical approaches of X-ray and NMR, with that of emerging computational–biochemical approaches, for structural elucidation specifically for AID/APOBEC3s.